Endovascular treatment of patients with high-risk symptomatic intracranial vertebrobasilar stenoses: long - term outcomes. Issue 4 (2nd June 2019) - Djurdjevic, Tanja; Cunha, André; Schulz, Ursula; Briley, Dennis; Rothwell, Peter; Küker, Wilhelm
Abstract : Background and purpose: We present the long-term outcome after endovascular treatment of symptomatic intracranial posterior circulation stenoses. Methods: 30 patients with symptomatic intracranial posterior circulation stenoses exceeding 70% underwent endovascular treatment between 2006 and 2012. Data regarding presentation, follow-up, procedure details, complications and imaging follow-up were reviewed. All surviving patients underwent a phone interview to establish their current Modified Ranking Scales (MRS). Results: Stenoses of the intracranial vertebral artery (24 patients) and basilar artery (6 patients) were treated with stents (10 patients), angioplasty alone (13 patients) or both (5 patients). Two procedures failed. One patient (3.3%) died after the procedure, two had stroke (6.6%) and one a subarachnoid haemorrhage without ensuing deficit. Two patients (6.7%) had asymptomatic complications (dissection and pseudoaneurysm). The median clinical follow-up time was 7 years. Of the 29 patients who survived the procedure, 6 died due to unrelated causes. Three patients (10%) had recurrent strokes and two (6.7%) a transient ischaemic attack in the posterior circulation. Two patients had subsequent middle cerebral artery strokes. Five (16.7%) patients had recurrent stenoses and three (10%) occlusions of the treated artery. Retreatment was performed in six patients, three (10%) with PTA and three (10%) with stenting. Current MRS scores were as follows: nine MRS 0, eight MRS 1, four MRS 2 and one MRS 4. Conclusions: Long-term follow-up after endovascular treatment of high-risk symptomatic intracranial posterior circulation stenoses shows few stroke recurrences. Treatment of intracranial vertebral artery stenosis may be beneficial in appropriately selected patients.